HER2 in solid tumors: more than 10 years under the microscope; where are we now?. (June 2014) - Martin, Vittoria; Cappuzzo, Federico; Mazzucchelli, Luca; Frattini, Milo
ABSTRACT: : HER2 is a well-recognized mediator of the cancerogenic process. It is dysregulated in a wide range of solid tumors, mainly via protein overexpression and/or gene amplification, thus making HER2 an attractive target for tailored treatment. The anti-HER2 therapy trastuzumab was approved for the treatment of HER2-positive metastatic breast cancer patients more than 10 years ago. Since then, trastuzumab and other HER2-inhibitors have been entered into clinical practice for the treatment of breast cancer and, more recently, have been approved to treat HER2-positive metastatic gastric cancers. Currently, HER2-targeted therapies are under evaluation in other tumor types. Due to the relevance of proper patient selection, the accurate assessment of HER2 status is fundamental. This review will discuss the established knowledge and novel insights into the HER2 story, mainly focusing on breast, gastric and colorectal cancers, as well as providing a brief overview of salivary gland, bladder, ovarian and lung tumors.